2020
DOI: 10.1155/2020/7970265
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Prostate Cancer Evolution: Effect of Immunotherapy Based on Controlled Vaccination Strategy

Abstract: Basic immunology research over several decades has led to an improved understanding of tumour recognition by components of the immune system and mechanism of tumour evasion from immune detection. These findings have ultimately led to creating antitumour immunotherapies in patients with different kind of cancer including prostate cancer. The increasing number of reports confirms that immune-based therapies have clinical benefit in patients with prostate cancer with potentially less toxicity in comparison with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…Although this paper is not a theoretical study, the intention is to present a mathematical model around prostate cancer and immunotherapy to show a mathematical relationship between the different variables and immunotherapy action as part of the prostate cancer disease. The models presented here are adopted from the work done by Kronik et al [26] and Badziul et al [27], as follows:…”
Section: 1mathematical Prostate Cancermentioning
confidence: 99%
“…Although this paper is not a theoretical study, the intention is to present a mathematical model around prostate cancer and immunotherapy to show a mathematical relationship between the different variables and immunotherapy action as part of the prostate cancer disease. The models presented here are adopted from the work done by Kronik et al [26] and Badziul et al [27], as follows:…”
Section: 1mathematical Prostate Cancermentioning
confidence: 99%
“…We build on previously proposed mathematical models of PCa response to ADT [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ], as well as models of tumor-immune interactions (we refer the reader to [ 29 , 30 ] for recent reviews). Recent studies have also reported models of PCa response to vaccination alone [ 31 , 32 ] or in combination with ADT [ 33 ]. Our approach differs from these in three major respects.…”
Section: Introductionmentioning
confidence: 99%